Predominant Role of Water in Native Collagen Assembly inside the Bone Matrix - Rai, Ratan Kumar; Singh, Chandan; Sinha, Neeraj (The journal of physical chemistry. B, 2015)
Bone is one of the most intriguing biomaterials found in nature consisting of bundles of collagen helixes, hydroxyapatite, and water, forming an exceptionally tough, yet lightweight material. We present here an experimental tool to map water-dependent subtle changes in triple helical assembly of collagen protein in its absolute native environment. Collagen being the most abundant animal protein has been subject of several structural studies in last few decades, mostly on an extracted, overexpressed, and synthesized form of collagen protein. Our method is based on a 1H detected solid-state nuclear magnetic resonance (ssNMR) experiment performed on native collagen protein inside intact bone matrix. Recent development in 1H homonuclear decoupling sequences has made it possible to observe specific atomic resolution in a large complex system. The method consists of observing a natural-abundance two-dimensional (2D) 1H/13C heteronuclear correlation (HETCOR) and1H double quantum–single quantum (DQ-SQ) correlation ssNMR experiment. The 2D NMR experiment maps three-dimensional assembly of native collagen protein and shows that extracted form of collagen protein is significantly different from protein in the native state. The method also captures native collagen subtle changes (of the order of ∼1.0 Å) due to dehydration and H/D exchange, giving an experimental tool to map small changes. The method has the potential to be of wide applicability to other collagen containing biomaterials.